2015
DOI: 10.1002/j.2161-1912.2015.00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Cognitive Predictors of Academic Motivation Among Mexican American Adolescents: Caution Against Discounting the Impact of Cultural Processes

Abstract: This study examined the role of cognitive (i.e., grit, hope, and academic skepticism) and cultural variables (i.e., generational status, familismo, ethnic identity, and bicultural stress) on academic motivation among 181 Mexican American adolescents. Results indicated that hope, grit, and familismo positively predicted academic motivation. Conversely, academic skepticism and bicultural stress negatively predicted academic motivation. This study demonstrates that culture is important to consider above and beyon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…The 6-item Skepticism About the Relevance of School for Future Success Scale (Midgley et al, 2000) A mean of all six items was computed, with higher mean scores indicating that one is more skeptical about academic pursuits being relevant for future success in life. A previous study that used this measure with Mexican descent high school students demonstrated acceptable levels of internal consistency (α = 0.83; Piña-Watson et al, 2015).…”
Section: Academic Skepticismmentioning
confidence: 91%
See 2 more Smart Citations
“…The 6-item Skepticism About the Relevance of School for Future Success Scale (Midgley et al, 2000) A mean of all six items was computed, with higher mean scores indicating that one is more skeptical about academic pursuits being relevant for future success in life. A previous study that used this measure with Mexican descent high school students demonstrated acceptable levels of internal consistency (α = 0.83; Piña-Watson et al, 2015).…”
Section: Academic Skepticismmentioning
confidence: 91%
“…Sample items are: “I try hard in school,” “I usually finish my work on time,” and “education is important to me.” The five items were averaged, with higher means indicating higher levels of academic motivation. In a previous study with Latina/o adolescents, an acceptable internal consistency coefficient was achieved ( α = 0.73; Piña‐Watson, López, Ojeda, & Rodriguez, ). For the current study, α = 0.72.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have correlated grit with positive outcomes such as grade point average, teacher retention, and academic motivation (EskreisWinkler, Shulman, Beal, & Duckworth, 2014;Maddi, Matthews, Kelly, Villarreal, & White, 2012;Pina-Watson, Lopex, Ojeda, & Rodriguez, 2015;Strayhorn, 2014). Though these findings are impressive, researchers cautioned that the Grit Scale is a self-report measure that is focused largely on past events and in these studies, was not correlated with other variables such as self-efficacy that are associated with achievement (Duckworth et al, 2007;Eskreis-Winkler et al, 2014)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, research is needed on how and for whom socioemotional factors, like grit and emotional engagement, contribute to achievement (e.g., Becker & Luthar, ; Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, ), especially across age and with the outcome of literacy achievement among dual language learners (e.g., Taboada Barber & Gallagher, ). Although the link between grit and literacy achievement has not been examined, recent research has connected grit with motivation, including among Latina/o students (Eskreis‐Winkler, Shulman, Beal, & Duckworth, ; Piña‐Watson, López, Ojeda, & Rodriguez, ), and motivation has been found to predict elementary and middle school literacy achievement (see Guthrie, Wigfield, & You, , for review). Indeed, students’ motivation and engagement do predict literacy achievement, even after adjusting for previous literacy achievement (e.g., Meece, Wigfield, & Eccles, ), and among culturally and linguistically diverse elementary school students (e.g., Taboada, Tonks, Wigfield, & Guthrie, ).…”
Section: Introductionmentioning
confidence: 99%